Opinion Review of Socioeconomic Impact of COVID-2019 on Women's Health - Salami, Victory U.; Okoduwa, Stanley I. R.; Chris, Aimee O.; Ayilara, Susannah I.; Okoduwa, Ugochi J. (Frontiers in Global Women's Health, 2021)
The global community battled to survive the onslaughts of the Coronavirus Disease 2019 (COVID-19) since December 2019 till date. Women and girls have borne the brunt of the hardship resulting from the health crises. This paper examined the effects of COVID-19 on women. Socio-economic factors resulting from the pandemic, especially in relation to women’s health were discussed after studying published articles. They include Gender Specificity and COVID-19, Economic toll of COVID-19 on women, Pregnancy and COVID-19, Gender-based Violence due to COVID-19 and Healthcare Impacts of COVID-19. Women being majority in the health workforce were at higher risk of infection with COVID-19 due to their exposure as caregivers to infected patients. The pandemic took its toll on them as part of the greater population in the informal sector of the economy due to the lockdown directive as many experienced severe monetary shortages and job losses. Pregnant women infected with COVID-19 were prone to severe diseases, maternal complications and death due to their weakened immunity and exposure during clinical procedures. Gender-based violence was observed to have increased across the globe for women. The results of this review strongly indicate that women are disproportionately affected by the ongoing COVID-19 health crisis. This review will help healthcare professionals and policy makers arrive at properly-thought-through decisions to better manage health crises. Governments and all key players should address the challenge by devising effective policies with a gendered view.